2021
DOI: 10.1016/j.mcpro.2021.100073
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Redox Proteomic Analysis Highlights New Mechanisms of Sensitivity to Silver Nanoparticles

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Although DCP-NEt2C is specific for detection of oxidized thiols in mitochondria, we observed DCP-Net2C labeling to be correlated with other metrics of total thiol oxidation in lung cells treated with AgNPs [ 13 ]. Furthermore, we previously found that an increase in sulfenylated proteins following AgNP treatment was characteristic of AgNP sensitive breast and lung cancer cells using biotinylated, dimedone-based probes to detect protein sulfenic acids by western blot [ 9 ], and by quantification of total reversible protein thiol oxidation using mass spectrometry [ 14 ]. The second method we used here to assess proteotoxicity involved staining with proteostat after paraformaldehyde fixation for the formation of protein aggregates in AgNP-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DCP-NEt2C is specific for detection of oxidized thiols in mitochondria, we observed DCP-Net2C labeling to be correlated with other metrics of total thiol oxidation in lung cells treated with AgNPs [ 13 ]. Furthermore, we previously found that an increase in sulfenylated proteins following AgNP treatment was characteristic of AgNP sensitive breast and lung cancer cells using biotinylated, dimedone-based probes to detect protein sulfenic acids by western blot [ 9 ], and by quantification of total reversible protein thiol oxidation using mass spectrometry [ 14 ]. The second method we used here to assess proteotoxicity involved staining with proteostat after paraformaldehyde fixation for the formation of protein aggregates in AgNP-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies show that some breast cancer cell lines are more sensitive to AgNP exposure than non-neoplastic mammary epithelial cells [ 9 11 ]. Similarly, there is substantial variability in the sensitivity of ovarian cancer [ 12 ], lung cancer [ 13 , 14 ], and leukemia cell lines [ 15 ] to AgNP exposure. Our previous recent results show that sensitivity to Ag + exposure does not correlate with sensitivity to intact AgNPs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium-metallofullerenol nanoparticles blocked epithelial-to-mesenchymal transition in triple-negative breast cancer (TNBC) and eliminated breast cancer stem cells (CSCs) [21]. Furthermore, we previously observed that AgNPs selectively eliminate certain TNBCs, ovarian cancer cells, and NCSLC with a mesenchymal phenotype [23,27,29,33]. Reports indicate that certain nanoparticles, including iron-core nanoparticles [70,71], titanium dioxide (TiO2) [72], ultrasmall poly (ethylene glycol)-coated silica nanoparticles [73], cobalt NPs [74], and manganese silicate nanobubbles [75], induce lipid oxidation in a variety of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that certain breast cancer cell lines are more sensitive to silver nanoparticle (AgNP) exposure than non-malignant mammary epithelial cells [23][24][25][26]. Notably, AgNP exposure increases protein oxidation and proteotoxic stress [23][24][25][27][28][29] and may cause lipid peroxidation in certain cells and organisms [30][31][32]. However, there is considerable heterogeneity in the relative sensitivity of various cancers to AgNP exposure [23][24][25]27,29,33,34], and it is not known if cancers with an EMT phenotype are more susceptible than other cancers or normal cells to proteotoxic stress or lipid peroxidation caused by exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 99%